Pengaruh Lama Naungan dan Jarak Tanam terhadap Pertumbuhan dan Hasil Bawang Merah (Allium Ascalonicum L.) Asal Biji - Sri Utami, Nindy Yuja; Armaini, Armaini; Irfandri, Irfandri (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
Productivity of shallots can be increased through the use of seeds derived from seeds. However, seed growth in the field requires effective growth requirements and avoids full sun exposure. For this reason, it is necessary to study the shade time and determine the planting distance that can support the growth of seeds in the hope of obtaining the best shade time and planting distance to obtain tubers as seeds. The study was conducted in the Experimental Garden of the Faculty of Agriculture, University of Riau, Pekanbaru in March to May 2019. The study used a divided plot design, the shade time as the main plot is without shade, for 3 weeks and 6 weeks. planting distance as subplot is 5 cm x 10 cm, 7,5 cm x 10 cm, 10 cm x 10 cm and 12,5 cm x 10 cm. The research data were further tested with a LSD level of 5%. The parameters observed were plant height, number of leaves, tuber diameter, fresh weight, dry weight of the eskip and tuber weight loss. Planting distance of 10 cm x 10 cm with a shade period of 6 weeks has a good effect on fresh weight and dry weight of the eskip. The shade time 6 weeks has a good effect on growth, tuber diameter, dry weight and dry weight of the eskip, while the planting distance of 10 cm x 10 cm affects both the fresh weight and dry weight of the eskip.Keywords: Shallot, shade time, planting distance